At the Origins of European Sovereignty: Peer-reviewed article (Italian Review of Legal History, 2022)
This essay aims at retracing in a new light the legal and historical roots of the controversial concept of “popular sovereignty” in the European context. To this purpose, it could be useful to analyse the last great debate on sovereignty, occurred in Germany during the Weimar Republic, before the oncoming storm of Nazism. Beyond the differences, today as yesterday the real issueat stake has been the problematic relationship between Europe and sovereignty. Just consider the significant diatribe between the philosopher Jürgen Habermas and the jurist Dieter Grimm that took place at the beginning of the process of European integration as well as the controversy on the future of Europe between Habermas and the sociologist Wolfgang Streeck. In such still open debate, concepts and categories from the Weimar lexicon are re-emerging. An emblematic example is the concept of “people”, whose meaning is ambiguous, as evidenced by its linguistic and conceptual history.
Keywords: Popular Sovereignty; European Integration; Weimar Republic; Carl Schmitt; Hans Kelsen; Hermann Heller